Neonatal early-onset sepsis calculator: Impact on antibiotic use in a level II neonatal unit in Western Australia - John Gannon; Tobias Strunk; Noel Friesen; Chia Saw (Pediatrics and Neonatology)
Background: Overuse of empirical intravenous antibiotics in neonates in high-income countries (HICs) is well documented. The Kaiser Permanente neonatal early-onset sepsis (EOS) calculator is an evidence-based sepsis risk assessment tool that has demonstrated potential to reduce antibiotic usage in this population. The incidence of early-onset sepsis in most HICs is 0.4–0.8 per 1000 live births. The objective was to evaluate the calculator's impact on antibiotic rates and length of stay in a regional level II Special Care Nursery. Methods: A single-centre retrospective cohort study compared antibiotic administration rates in the first 72 h in neonates ≥35 weeks gestation born during two 6-month periods in 2019 (pre-EOS calculator) and 2021 (post-EOS calculator). Electronic and paper case records were accessed to capture data. Continuous data were summarised using mean and standard deviation, and categorical data were summarized using frequency distributions. There were 951 (2019) and 1129 (2021) infants born during the study periods. Results: Following implementation of the calculator, antibiotic exposure decreased from 13.7% to 4.7% of all neonates without reported negative outcomes. Mean length of stay for neonates born across the two periods decreased from 2.38 to 2.13 days. Indications for antibiotic use shifted more towards clinical condition and away from obstetric risk factors. There were no culture-proven cases of sepsis or readmissions with EOS in either period. Conclusion: Implementation of the EOS calculator significantly reduced exposure to antibiotics, without adverse outcomes.